Siri na pacce: From the ethnic culture to the theological social solidarity - Wiryadinata, Halim (KURIOS, 2024)
This study shows how the ethnic culture of Bugis-Makassar, Siri Na Pacce, becomes the value of theological solidarity. The philosophical Siri Na Pacce, which upholds being part of the suffering’s others, becomes the foundation of theological solidarity. The migration of philosophical of Siri Na Pacce becomes religious values of social solidarity. The collision of religion and culture triggers this migration to form theological solidarity. The sociology of religion method expounds the philosophical value through analysis and evaluation of the local culture of Siri Na Pacce. This method accesses books, articles, academic writing, and related sources. The result of this research is that the migration of Siri Na Pacce values has rooted in Indonesian people in building a theological foundation of solidarity among the sufferings. In conclusion, the metamorphosis of Siri Na Pacce to Theological Social Solidarity shares values for religion and culture in Indonesia and extends its legacy to further generations.